Advances in immune mechanisms and developing immune-targeted therapies for osteoporosis: a systematic review - Tao, Ranyang; Liu, Chaoran; Wong, Pui Yan; Huang, Tao; Alt, Volker; Rupp, Markus; Jantsch, Jonathan; Thebault, Pascal; Labat, Beatrice; Ladam, Guy; Brochhausen, Christoph; Ip, Margaret; et al. (Pharmacological research, 2025)
Osteoporosis is characterized by the widespread deterioration of bone mass and microarchitecture. It poses an increasingly significant socioeconomic threat in light of the aging population. Emerging research highlights the crucial role played by crosstalk between bone cells and other components in the skeletal system, including immune cells, to maintain bone homeostasis. Despite articles introducing this novel field known as osteoimmunology, accumulating evidence has revealed that the role of the immune system in bone homeostasis extends beyond its previously recognized contributions. Therefore, we have performed a systematic review with the aim of synthesizing the existing literature on this particular topic, thereby offering readers a unified framework for immune-mediated bone regulation. A literature search was performed in PubMed, Embase and Web of Science. A total 16,021 results were found, and 150 articles were included following PRISMA guidelines. The involvement of the immune system in osteoporosis can be summarized into three primary aspects, providing a comprehensive overview for readers from diverse backgrounds: (1) the altered immune system in osteoporosis pathogenesis; (2) molecular pathways of immune system regulating bone homeostasis; and (3) current strategies targeting the immune system for therapeutic interventions. We found that the immune system not only responds to developmental changes through altered expression and differentiation but also mediates signals from other tissues to influence bone phenotype. We present a framework of osteoimmunology that can inform the development of new clinical strategies and biomaterials, highlighting immune cells as mediators of signals from other organs or tissues.
Online verfügbar: 21. Juni 2025, Artikelversion: 26. Juni 2025
Gesehen am 21.08.2025